Strengthening of the Restored Surface Layer of Steel Parts 45 by Laser Boring - Cherneta, Oleg; Kubich, Vadim; Voloshchuk, Roman; Averyanov, Vladimir; Shmatko, Dmytro; ., . (International Journal of Engineering and Technology, 2018)
By means of the proposed technologies, the relationship and strengthening of the optimal modes of recovery of the restoring layer and the optimal laser treatment modes with bat-retaining straps are chosen. The microstructural, X-ray diffraction studies of the restored surfaces of the cams of the distributing shaft of the car were determined, the wear resistance and microhardness of the working surfaces were determined. By means of the proposed technologies of restoration and strengthening, optimum modes of applying the restoring layer and optimal modes of laser treatment (pumping energy of 20 kJ without melting of the surface) with bat-retaining coatings (thickness 2 mm) were chosen. The unevenness of the pulsed laser treatment with the restriction of the diameter of the laser spot and the treatment of a boron-rich surface layer with overlapping of the corresponding zones leads not only to the quenching but also to the release of individual local microparticles. New phases such as boron carbide, carbides - borides, iron borides, and others are formed. The strengthened surface layer has a complex structure and generally contains a martensite base with thin layers of borides, Ñarbides. The microhardness of the processing zone rises 3-4 times (ÐÎ¼ 6500-7000 MPa).Â Â